Cross‐boundary working: Implications for HRM theory, methods, and practice. (23rd May 2019) - Kinnie, Nicholas; Swart, Juani
Abstract: Major changes have taken place in work organisation, which originate predominantly from working across organisational boundaries. This paper argues for a more sophisticated approach to HRM that includes three types of cross‐boundary working, that is, intraorganisational, interorganisational, and transorganisational. Herein lies the contribution of our paper; we argue that we cannot assume a transition from one type of working to another because cross‐boundary forms of working coexist. We also need to understand the tensions of this simultaneity at the levels of the organisation/network, HRM systems, and the individual. We consider the impact of the simultaneous existence of these types of cross‐boundary working for the following: (a) theory, especially the development of HRM systems; (b) methods, including an activity‐based unit of analysis; and (c) practice, where we pay attention to the challenges of control, collaboration, and consistency.